1998
DOI: 10.1016/s0304-3959(98)00133-x
|View full text |Cite
|
Sign up to set email alerts
|

The control of severe cancer pain by continuous intrathecal infusion and patient controlled intrathecal analgesia with morphine, bupivacaine and clonidine

Abstract: The management of severe cancer pain may be problematic in spite of recent advances in pain management. A small percentage of patients with severe intractable pain and/or intractable side effects may require more aggressive interventional pain management strategies including the administration of medications continuously by the intrathecal route. A variety of medications, including morphine, bupivacaine, and clonidine, may be used intrathecally for the control of cancer pain. Optimal use of these medications r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…As a result, drugs that produced intolerable side effects when used orally or intravenously may be well tolerated intrathecally. Often, several different medications are combined to control various facets of "complicated" pain or to keep overall side effects low [7].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, drugs that produced intolerable side effects when used orally or intravenously may be well tolerated intrathecally. Often, several different medications are combined to control various facets of "complicated" pain or to keep overall side effects low [7].…”
Section: Discussionmentioning
confidence: 99%
“…This medication is almost always used in conjunction with other agents, especially if there is a strong neuropathic component to the pain. Tumber and Fitzgibbon [ 33 ] described a patient who required a "cocktail" of continuous intrathecal medications that included clonidine for pain control due to his inoperable sacral chordoma. In the review by Baker et al [ 29 ], clonidine was reportedly used in approximately one third of patients for better pain control.…”
Section: α 2-adrenergic Agonistsmentioning
confidence: 99%
“…Although 82% of patients found that their ability to perform the activities of daily living improved, 3.8% reported a decrease in this indicator. Analysis of dosage by diagnosis revealed that dosing was significantly Onofrio et al [4] Morphine µ opioid Cancer Hassenbusch et al [5] Neuropathic Anderson and Burchiel [6] Benign Goodman and Brisman [7] CRPS Coombs et al [8] Hydromorphone µ opioid Cancer Harvey et al [9] Meperidine µ opioid Benign Max et al [10] Methadone µ opioid Cancer Meignier et al [11] Fentanyl µ opioid Cancer Devulder [12] Sufentanil µ opioid Neuropathic Oyama et al [13] β-endorphin µ opioid Cancer Moulin et al [14] DADL δ opioid Cancer Wen et al [15] Dynorphin κ opioid Cancer Schoeffler et al [16] Midazolam GABA-A agonist Cancer Borg and Krijnen [17] Benign Zuniga et al [18••] Baclofen GABA-B agonist Neuropathic Tumber et al [19] Clonidine α-2 adrenergic Cancer Siddall et al [21] Neuropathic Eisenach et al [22] Experimental Borg and Krijnen [17] Benign Sjoberg et al [23] Bupivacaine Na + channel antagonist Cancer Nitescu et al [24] Benign Penn and Paice [25] Ziconotide Ca ++ channel antagonist Cancer Brose et al [26•] Neuropathic Staats et al [27] Yang et al [28] Ketamine NMDA antagonist Cancer Kristensen et al [29] CPP NMDA antagonist Neuropathic Penn [30] Octreotide Somatostatin Cancer Paice et al [31] Benign Karlesten and Gordh Jr [32] R-PIA Adenosine analogue Neuropathic Klamt et al [33] Neostigmine AChase inhibitor Cancer Devoghel [34] Aspirin COX inhibitor Cancer Pellerin et al [35] Benign COX-cyclooxygenase; CPP-3-(2-carboxypiperazin-4-yl)propyl-1-phosphonic acid; CRPS-complex regional pain syndrome; DADL-[D-Ala2,D-Leu5]-enkephalin; GABA-gamma-aminobutyric acid; NMDA-N-methyl-D-aspartate; R-PIA-R-phenylisopropyl-adenosine.…”
Section: Available Intrathecal Drugsmentioning
confidence: 99%
“…In addition, ␣-2 adrenoceptor agonists increase potassium conductance and hyperpolarize dorsal horn neurons. Clinically, clonidine is effective in the treatment of cancer pain, neuropathic pain, chronic benign pain, experimental hyperalgesia, and spasticity [19,21,22,42]. The reported dose range for clonidine is 17 to 1500 µg/24 h, with a usual starting dose of 75 to 150 µg/ 24 h. Because ␣-2 adrenoceptor agonists also decrease sympathetic outflow, the ability to achieve effective analgesia with monotherapy is frequently limited by hypotension, bradycardia, and sedation.…”
Section: ␣-2 Adrenoceptor Agonistsmentioning
confidence: 99%